Analisis Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Potensi Kredit Bermasalah pada Lembaga Perkreditan Desa dan PT Bank BRI (Persero) Tbk di Kecamatan Kintamani (Studi Pada LPD Desa Pakraman Dausa dan Bank BRI Unit Kintamani, Kec. Kintamani, Bangli, Bali) - Muliani, Ni Luh Mega (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to investigate the influence of internal factors and external factors on problem loans at Village Credit Institutions ( LPD ) and Bank BRI in the district of Kintamani , Bangli , Bali . The author uses the non-performing loans as the dependent variable and enter the variable internal factors and external factors as independent variables The author uses quantitative research methods and using multiple linear regression analysis to see how big the effect that the test then the difference between LPD and Bank BRI .The results showed that the variables of internal factors and external factors significant and positive impact on non-performing loans in the Village Credit Institutions ( LPD ) and Bank BRI in the district of Kintamani , Bangli , Bali .Keyword : NPL , Factor Internal , External Factors